Steps toward determination of the size and structure of the broad-line region in active galatic nuclei. 8: an intensive HST, IUE, and ground-based study of NGC 5548 - ESPEY, BRIAN RUSSELL (My University, 1995)
We present the data and initial results from a combined Hubble Space Telescope (HST)/IUE/ground-based spectroscopic monitoring campaign on the Seyfert 1 galaxy NGC 5548 that was undertaken in order to address questions that require both higher temporal resolution and higher signal-to-noise ratios than were obtained in our previous multiwavelength monitoring of this galaxy in 1988-1989. IUE spectra were obtained once every 2 days for a period of 74 days beginning on 1993 March 14. During the last 39 days of this campaign, spectroscopic observations were also made with the HST Faint Object Spectrograph (FOS) on a daily basis. Ground-based observations, consisting of 165 optical spectra and 77 photometric observations (both CCD imaging and aperture photometry), are reported for the period 1992 October-1993 September, although many of the data are concentrated around the time of the satellite-based program. These data constitute a fifth year of intensive optical monitoring of this galaxy. In this contribution we describe the acquisition and reduction of all of the satellite and ground-based data obtained in this program. We describe in detail various photometric problems with the FOS and explain how we identified and corrected for various anomalies.
PUBLISHED
Keywords: Physics